Performance analysis framework for NOMA systems over non-identical nakagami-m fading channels - Tregancini, Anderson [UNESP]; Lima, Carlos H. M.; Olivo, Edgar E. Benitez [UNESP]; Alves, Hirley (Institute of Electrical and Electronics Engineers (IEEE), 2019)
This paper proposes an analytical framework based on the H-function distribution to study the performance of non-orthogonal multiple access (NOMA)-based wireless networks. More specifically, herein we investigate the outage performance and the ergodic capacity of a three-node linear network topology where a source uses power-domain NOMA to communicate with two destinations over independent, but not necessarily identically distributed Nakagami-m fading channels. A Monte Carlo simulations campaign was carried out to support the proposed framework.
Keywords: Ergodic capacity; H-function distribution; Nakagami-m; NOMA; Outage probability